THE EFFECT OF INTERACTIVE MULTIMEDIA-SUPPORTED DISCOVERY LEARNING MODELS ON STUDENT LEARNING OUTCOMES IN ECONOMICS - Siagian, Maya Sari; Armiati (JURNAL PENDIDIKAN GLASSER, 2025)
Economics education is essential for developing students’ critical and analytical thinking, especially in understanding socio-economic issues. However, conventional teaching methods, which still dominate, often result in passive learning and low achievement. This is also evident at SMA Negeri 5 Bukittinggi, where most Grade XI students fail to meet the Minimum Competency Criteria (KKM). Observations and questionnaires reveal that learning tends to be monotonous with minimal student engagement. To overcome this, more interactive and student-centered approaches are needed. This study investigates the effect of the discovery learning model assisted by interactive multimedia on student learning outcomes. A quasi-experimental method with a nonequivalent control group design was used. Two purposively selected classes were involved one as the experimental group, the other as the control group. Data were gathered through pre-tests and post-tests, and analyzed using an independent t-test and N-Gain. Results show that discovery learning supported by multimedia significantly improved outcomes. The experimental group scored an average of 72.34, while the control group scored 57.55, indicating moderate improvement. The findings suggest that this model can serve as an effective alternative for enhancing student participation and achievement in economics learning